2020
DOI: 10.3389/fvets.2020.00343
|View full text |Cite
|
Sign up to set email alerts
|

Higher Bioavailability of Calcium in Chickens With a Novel In-Feed Pharmaceutical Formulation

Abstract: Egg production and egg shell quality decrease toward the end of the first laying cycle in hens (approximately by week 80). Even so, farmers often choose to work a second cycle with them. Defective egg shell production has been mainly linked to a decrease in gastrointestinal absorption of calcium. Here we studied pharmaceutically-designed modified-release small pellets (FOLAs) containing calcium to improve calcium bioavailability (F). The influence of FOLA alone or with capsicum-oleoresin was studied in a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Hence, production was maintained as efficiently as that observed in first cycle hens. (12,14) Nevertheless, it may be possible that the supplementation with turmeric powder and cinnamon powder could have assisted the formulation of FOLA-pellets described here, as it has been shown that these phytoelements improve various performance parameters in poultry. (43,44) To ponder these results, and despite the benefits outlined, it will be of particular interest to carry out economic studies in hens that produce eggs for human consumption, as well as in hens producing fertile eggs for broiler production.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, production was maintained as efficiently as that observed in first cycle hens. (12,14) Nevertheless, it may be possible that the supplementation with turmeric powder and cinnamon powder could have assisted the formulation of FOLA-pellets described here, as it has been shown that these phytoelements improve various performance parameters in poultry. (43,44) To ponder these results, and despite the benefits outlined, it will be of particular interest to carry out economic studies in hens that produce eggs for human consumption, as well as in hens producing fertile eggs for broiler production.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, FOLA-pellets are obtained by extruding corn and wheat flour (1:1) containing modified release vehicles (mentioned in the referred patent), plus 4.1 % calcium-carbonate. (12,14) Animals A total of 180 Bovans-White weighing 1 570 ± 20 g, laying hens in a second cycle (> 180 weeks old) and 180 Bovans-White hens in the third cycle (> 270 weeks of age), were included in this trial carried out from August to Mid December 2022. To test FOLA pellet subjected to environmental heat stress, further 90-second and third-cycle Bovans-White hens were studied for egg production and eggshell thickness during May 2023, the hottest period of the year in the central part of Mexico, reaching temperatures at or above 30 °C.…”
Section: Development Of the Preparationsmentioning
confidence: 99%
See 3 more Smart Citations